Facile preparation of magnetic graphene double‐sided mesoporous composites for the selective enrichment and analysis of endogenous peptides. Issue 15 (1st July 2013) - Yin, Peng; Sun, Nianrong; Deng, Chunhui; Li, Yan; Zhang, Xiangmin; Yang, Pengyuan
<x xml:space="preserve">Abstract</x> In this work, magnetic graphene double‐sided mesoporous nanocomposites (mag‐graphene@mSiO2) were synthesized by coating a layer of mesoporous silica materials on each side of magnetic grapheme. The surfactant (CTAB) mediated sol‐gel coating was performed using tetraethyl orthosilicate as the silica source. The as‐made magnetic graphene double‐sided mesoporous silica composites were treated with high‐temperature calcination to remove the hydroxyl on the surface. The novel double‐sided materials possess high surface area (167.8 cm2/g) and large pore volume (0.2 cm3/g). The highly open pore structure presents uniform pore size (3.2 nm) and structural stability. The hydrophobic interior pore walls could ensure an efficient adsorption of target molecules through hydrophobic–hydrophobic interaction. At the same time, the magnetic Fe3O4 particles on both sides of the materials could simplify the process of enrichment, which plays an important role in the treatment of complex biological samples. The magnetic graphene double‐sided nanocomposites were successfully applied to size‐selective and specific enrichment of peptides in standard peptide mixtures, protein digest solutions, and human urine samples. Finally, the novel material was applied to selective enrichment of endogenous peptides in mouse brain tissue. The enriched endogenous peptides were then analyzed by LC‐MS/MS, and 409 endogenous peptides were detected and identified. The results demonstrate that the as‐made mag‐graphene@mSiO2 have powerful potential for peptidome research.